Learning leadership and feedback seeking behavior: Leadership that spurs feedback seeking - Crans, Samantha; Aksentieva, Persiana; Beausaert, Simon; Segers, Mien (Frontiers in Psychology, 2022)
Lifelong learning is crucial for professionals to continuously develop and update their knowledge and skills, and for organizations to create and sustain competitive advantage. In this regard, feedback seeking is a powerful vehicle to gain new knowledge and insights in one’s development and performance. The current research dives deeper in the concept of feedback seeking by investigating the act and use of feedback as well as multiple feedback seeking methods. Leadership as a contextual factor can affect employees’ feedback seeking behavior. As such, this study also explores the role of learning leadership for feedback seeking. Learning leadership supports, facilitates and encourages employees’ professional development. To address these aims, two independent studies were conducted. Study 1 was a quantitative, survey study that investigated the direct relationship between learning leadership and (the act and use of) feedback seeking. Study 2 was a qualitative, interview study that explored which concrete learning leadership behaviors were linked to different methods of feedback seeking. The findings confirmed the pivotal role of leaders in employees’ feedback seeking behavior and provided an overview of concrete learning leadership behaviors.